Burnout syndrome and mental Health of nursing professionals in the Covid-19 pandemic (Research, Society and Development, 2022)
Objective: to carry out an integrative review about the relationship between Burnout syndrome, factors involved in the mental health of nursing professionals and the Covid-19 pandemic. Methodology: this is an integrative literature review carried out through scientific articles from the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and Medline via PubMed. The inclusion criteria for this research were: original and/or review studies, with publication date between 2020 to 2022 in Portuguese, filtered with the descriptors: “Burnout Syndrome”, “Professional Exhaustion”; “Nursing Professionals”; “Covid-19” and “Mental Health Assistance”, for selection of articles used in the review. Results: twenty articles were identified, divided into three categories: emphasis on work overload, emphasis on mental health and emphasis on professionals' perception. Conclusion: depression, anxiety, insomnia, work overload, long hours, fear of contamination and sudden loss of patients were the most prevalent factors cited for triggering Burnout syndrome in nursing professionals, in addition to the lack of human and material resources. and professional appreciation.